Community-based rehabilitation for older adults post-stroke in Thailand: An ethnographic study - Somtua, Niramol; Nuntaboot, Khanitta (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Stroke is a leading cause of disability among older adults, with long-term effects on their independence and quality of life. In Thailand, while previous studies have explored aspects of post-stroke rehabilitation, there remains a gap in understanding how to effectively integrate healthcare services, community resources, and cultural practices into a comprehensive, sustainable rehabilitation model. Objective: This study aimed to explore community-based rehabilitation for older adults post-stroke in Thailand. Methods: An ethnographic research design was employed to examine community-based rehabilitation practices. Participants included 88 key informants, comprising older adults post-stroke (n = 21), family members (n = 24), local administrative officials (n = 7), healthcare professionals, caregiver representatives, public health volunteers, village/sub-district headmen (n = 12), community organization members (n = 15) and general informants (neighbors and relatives) (n = 9). Data collection methods included participant observation, in-depth interviews, group discussions, and document reviews conducted from May 2023 to August 2024. Content analysis was applied, with triangulation ensuring data validity. Findings were further confirmed by informants and qualitative research experts. Results: Community-based rehabilitation for older adults post-stroke consisted of three interconnected domains: 1) Support Systems and Infrastructure, including family caregiver involvement, healthcare services, emergency care, community rehabilitation programs, and public services; 2) Social and Economic Support, encompassing community welfare initiatives, volunteer networks, financial stability measures, and legal protections; and 3) Administrative and Management Systems, comprising integrated planning for older adults, data and information management, welfare accessibility, and culturally embedded care approaches. These elements created a comprehensive and sustainable rehabilitation framework. Conclusion: The study highlights the importance of an integrated rehabilitation system that combines healthcare, socioeconomic support, and administrative mechanisms. Findings emphasize the need for advanced training in case management and coordination for community nurses and call for culturally sensitive rehabilitation protocols that merge traditional Thai healing practices with contemporary medical care. These findings align with global recommendations for sustainable rehabilitation and highlight the importance of culturally sensitive approaches. Strengthening formal and informal care networks can enhance rehabilitation outcomes and improve the quality of life for older adults post-stroke.